2018
DOI: 10.1111/pedi.12717
|View full text |Cite
|
Sign up to set email alerts
|

One potato, two potato,… assessing carbohydrate counting accuracy in adolescents with type 1 diabetes

Abstract: Less than half of the teens in our study were accurate CHO counters. These results indicate the need for regular clinical accuracy check and reeducation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Having a higher A1C was associated with a lower likelihood of carbohydrate counting accuracy. This finding is consistent with evidence suggesting that carbohydrate counting may have beneficial effects on A1C in youth (35) and with our previous study showing that higher A1C was associated with lower accuracy on the tray test (7). Our findings suggest that greater ability to count carbohydrates over the preceding 3 months may affect mean blood glucose measures through adjustments in premeal insulin doses, leading to lower A1C.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Having a higher A1C was associated with a lower likelihood of carbohydrate counting accuracy. This finding is consistent with evidence suggesting that carbohydrate counting may have beneficial effects on A1C in youth (35) and with our previous study showing that higher A1C was associated with lower accuracy on the tray test (7). Our findings suggest that greater ability to count carbohydrates over the preceding 3 months may affect mean blood glucose measures through adjustments in premeal insulin doses, leading to lower A1C.…”
Section: Discussionsupporting
confidence: 92%
“…This randomized, controlled, parallel-group trial compared the effectiveness of teaching principles of carbohydrate counting to adolescents with type 1 diabetes who did not selfidentify as regular carbohydrate counters (ClinicalTrials.gov Identifier: NCT02462785). As in our previous study in adolescents with type 1 diabetes who self-identified carbohydrate counting as part of their diabetes management (7), we used two methods of assessing carbohydrate estimation knowledge and accuracy: 1) carbohydrate content estimations from trays of real prepared meals and snacks and 2) a validated questionnaire to assess knowledge of carbohydrate content (the PedsCarbQuiz [PCQ]) (26). However, in the current study, we compared two educational methods: 1) an in-class session (current standard of care) and 2) an Internetbased education module.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…For example, the results of a 2016 study of 61 adult T1D patients found that only 59% of the participants were able to achieve a satisfactorily accurate determination of carbohydrate content [6]. A recently published study on adolescents found that carbohydrate counting is more of a problem for them than for adults, which is not surprising [7].…”
Section: Discussionmentioning
confidence: 99%
“…When combined with supervision from healthcare professionals (registered dietitian or Certified Diabetes Care and Education Specialist), carbohydrate counting has been used as the gold standard for determining insulin dosing for PWD to maintain glycemic control [8,9]. Yet, carbohydrate counting is challenging; miss-estimation is common [10][11][12], and unfortunately, most PWD in the U.S. do not have access to multi-disciplinary care. Other challenges to carbohydrate counting include the time burden required for recording and calculating food intake and maintaining a stable weight within the dietary flexibility that carbohydrate counting allows [7].…”
Section: Introductionmentioning
confidence: 99%